Evaluation of the effect of nanoparticle addition into Gemini surfactant on rheology and wax deposition of Malaysian crude oil - Norida, Ridzuan; Wong, Wai Yan; Vijaya Kumar, Shamala Devi (Elsevier Ltd, 2022)
Crude oil is fossil fuel formed from the decomposition of decaying plants and animals in the ground. In crude oil, there is a high percentage of asphaltene that leads to wax deposition along the transport pipeline. The objective of this research is to study the effect of temperature, shear rate and nanoparticle loadings towards viscosity, interfacial tension, surface tension as well as the weight of wax deposit form. Two types of nanoparticles were used in this study, which were GOHSENX Anionic PVOH L-3266 and NICHIGO G-polymer AZF8035W. Whereas, Gemini YND1233 was used as a surfactant. Nanoparticle with different amount of loading (2 mg, 3 mg, 4 mg and 5 mg) was prepared using cyclohexane as the solvent. The nanofluid was prepared according to the load ratio of Gemini surfactant to nanoparticles of 3:1. With 5 mg of nanoparticle, L-3266 loading in Gemini surfactant showed the best performance where it resulted in the lowest viscosity, interfacial tension, surface tension and wax deposition as compared to the 2 mg of nanoparticle AZF8035W loading in Gemini surfactant. This is due to the carboxylic acid group present in AZF8035W. The optimum temperature and shear rate in reducing the crude oil viscosity was obtained at 35 °C and 80 rpm. In order to investigate the effect of nanoparticle loading and the stirring rate of impeller on the formation of wax deposit, the cold finger test had been conducted. From the cold finger analysis, the lowest weight of wax deposit was obtained at the cold finger temperature of 20 °C and the stirring rate of 500 rpm by adding 5 mg of nanoparticles L-3266 in Gemini surfactant. In conclusion, the best performance of wax inhibitor from this research was obtained by adding 5 mg of nanoparticles GOHSENX Anionic PVOH L-3266 in Gemini surfactant in order to improve the rheology of the crude oil and decrease the formation of wax deposition.